A Simple Nomogram for the Derivation of International Normalised Ratios for the Standardisation of Prothrombin Times - Poller, L (Thrombosis and Haemostasis, 1988)
The WHO international scale of reporting prothrombin time results is based on the calibration of local and commercial thromboplastin reagents used in the test against an international reference preparation to derive an International Sensitivity Index (ISI) for each batch of local reagent. This quantifies an individual reagent’s responsiveness to the coumarin induced defect.Once the ISI has been assigned, the derivation of International Normalised Ratios (INR) for reporting results depends on the use of a scientific calculator by which the local ratio is raised to the power of the ISI of the local reagent or use of an alternative formula and logarithms.A system for interpretation of INR, without the need for calculations, is presented for the known range of thromboplastins between 1.0 and 3.0 ISI in nomogram form. This chart may facilitate the general application of the INR system.
Keywords: Prothrombin time; Standardisation; International Normalised Ratios; International Sensitivity Index